Amphipods in a Greek cave with sulphidic and non-sulphidic water: phylogenetically clustered and ecologically divergent. Issue 6 (18th August 2019) - Borko, Špela; Collette, Martin; Brad, Traian; Zakšek, Valerija; Flot, Jean-François; Vaxevanopoulos, Markos; Sarbu, Serban M.; Fišer, Cene
Abstract : We characterized taxonomically, ecologically, and phylogenetically the amphipod community of Melissotrypa Cave (Central Greece), which comprises both freshwater and sulphidic lakes. We found four amphipod species: Niphargus jovanovici, Niphargus lindbergi, Niphargus gammariformis sp. nov. and an unknown species of Bogidiella. The three Niphargus species form a well-supported monophylum but differ in their ecology and morphology: N. jovanovici is a small and slender species inhabiting small freshwater voids, N. lindbergi is a large and stout species living in freshwater lakes, whereas N. gammariformis sp. nov. is a small and stout species found predominantly in a sulphidic lake. Available evidence suggests that diversification may have happened in a geographically restricted area and was driven by ecological differentiation. Niphargus gammariformis sp. nov. shows morphological convergences in diagnostic traits with two species hitherto classified into the genus Pontoniphargus. As molecular phylogenies show Pontoniphargus nested within Niphargus, we synonymize here Pontoniphargus with Niphargus . The species originally named Pontoniphargus ruffoi needed to be renamed into Niphargus pontoruffoi. http://www.zoobank.org/urn:lsid:zoobank.org:pub:4F5EED3B-DEB4-4402-BCE8-6AE2B65CCC3A